Determinant factor for dynamic equilibrium of transformation between vapor in atmosphere and water in concrete. (20th November 2020) - Gao, Furong; Ji, Yongsheng; Xu, Zhishan; Zhang, Zhongzhe; Zhou, Yangmei
Highlights: The RH in concrete is a constant of 100% as long as concrete pore is unsaturated. RH of the cavity is inaccurate to represent moisture condition of concrete. The determinant factor for water-to-vapor transformation is AH of the atmosphere. Abstract: Under certain conditions, liquid water in concrete pores can evaporate, forming vapor to the surrounding atmosphere; vapor in the surrounding atmosphere can condense, forming liquid water in concrete pores. Therefore, there exists a water-to-vapor transformation causing change of liquid water content in concrete. This study is aimed at analyzing the determinant factor for the water-to-vapor transformation based on the responses of relative humidity in concrete to different relative humidity and temperature of the surrounding atmosphere. Relative humidity in concrete was measured with two temperature and humidity (T&RH) probes (One was embedded into concrete and the other was placed in the cavity formed by embedding a PVC pipe) under two conditions: (1) constant temperature and variable relative humidity of the surrounding atmosphere (2) constant relative humidity and variable temperature of the surrounding atmosphere. Moreover, a specially designed device was adopted to verify the determinant factor for the water-to-vapor transformation. The results showed that relative humidity recorded by the embedded T&RH probe was always 100%, while that recorded by the placed T&RH probe had responses to the surrounding atmosphere under conditions (1) and (2). According to the results, the determinant factor for the water-to-vapor transformation is vapor partial pressure, namely absolute humidity, of the surrounding atmosphere. Furthermore, as long as there is liquid water in concrete, vapor in concrete pores is in saturation state, indicating the internal relative humidity of concrete should be a constant of 100%. Consequently, relative humidity in the cavity is inaccurate to represent moist condition of concrete.